2018
DOI: 10.1002/jcb.26535
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non‐coding RNA XIST suppresses nasopharyngeal carcinoma progression by activating miR‐491‐5p

Abstract: Dysregulated long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) play key roles in the development and progression of human cancers. X-inactive specific transcript (XIST), an lncRNA, is known as an oncogene in multiple tumors. However, the roles of XIST and its related miRNAs in nasopharyngeal carcinoma (NPC) are poorly understood. In this study, we found that XIST expression was significantly upregulated in NPC tissues and cell lines. Knockdown of XIST inhibited NPC cell proliferation and invasion and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
(57 reference statements)
1
14
1
Order By: Relevance
“…In our study, targeting XIST significantly reduced cell viability and increased cell apoptosis in vitro in U2OS cells, and targeting XIST suppressed tumorigenesis in vivo. Our findings are similar to those of the recent reports [31,32] and contrary to the results of recent reports [33,34]. However, the underlying mechanism by which XIST mediates gene expression and participates in tumorigenesis remains to be clarified.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, targeting XIST significantly reduced cell viability and increased cell apoptosis in vitro in U2OS cells, and targeting XIST suppressed tumorigenesis in vivo. Our findings are similar to those of the recent reports [31,32] and contrary to the results of recent reports [33,34]. However, the underlying mechanism by which XIST mediates gene expression and participates in tumorigenesis remains to be clarified.…”
Section: Discussionsupporting
confidence: 86%
“…In bladder cancer cells in vitro, targeting XIST suppressed cell invasion and proliferation by downregulation of p53 [30]. In nasopharyngeal carcinoma (NPC), targeting XIST inhibited NPC cell proliferation and invasion in vitro and NPC tumor growth in vivo [31]. Further investigation revealed that XIST acts as an oncogene in non-small cell lung cancer by epigenetically repressing KLF2 expression [32].…”
Section: Discussionmentioning
confidence: 99%
“…miR-491-5p was a tumor suppressor in several cancer types [ 20 23 ]. Aberrant expression of miR-491-5p was the consequence of upregulated circRNA circ_0001361 and lncRNA XIST in bladder cancer and nasopharyngeal carcinoma respectively [ 24 , 25 ]. In glioma, miR-491-5p was decreased in cancer tissues and correlated with good prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Knockdown of lncRNA XIST suppresses NPC progression by activating miR-491-5p. 24 SOX2-OT has been reported to be upregulated in laryngeal squamous cell carcinoma and regulate osteosarcoma cells proliferation and motility through modulating SOX2. 9,25 Nevertheless, the biological significance and regulatory mechanism of SOX2-OT in NPC progression are largely to be clarified.…”
Section: Discussionmentioning
confidence: 99%